2021
DOI: 10.3390/molecules26134060
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Serine-(NSAID) Hybrids with Anti-Inflammatory and Hypolipidemic Potency

Abstract: A series of L-serine amides of antioxidant acids, such as Trolox, (E)-3-(3,5-di-tert-butyl-4-hydroxyphenyl)acrylic acid (phenolic derivative of cinnamic acid) and 3,5-di-tert-butyl-4-hydroxybenzoic acid (structurally similar to butylated hydroxytoluene), was synthesized. The hydroxy group of serine was esterified with two classical NSAIDs, ibuprofen and ketoprofen. The Trolox derivatives with ibuprofen (7) and ketoprofen (10) were the most potent inhibitors of lipid peroxidation (IC50 3.4 μΜ and 2.8 μΜ), sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…The parent NSAIDs and antioxidants BHB, BHBA and Trolox have little or no inhibitory activity, except for Naproxen ( c ), and its reduced analog (alcohol) d , which exhibits IC 50 values of 25 and 29 μM, respectively. The little or no inhibition (IC 50 > 200 μM) of LOX-3 by most other parent NSAID molecules ( a – n ), as also observed in the literature [ 17 , 18 , 19 ], supports the fact that the incorporation of the two pharmacophores in one structure leads to an improved interaction with the enzyme.…”
Section: Resultssupporting
confidence: 76%
“…The parent NSAIDs and antioxidants BHB, BHBA and Trolox have little or no inhibitory activity, except for Naproxen ( c ), and its reduced analog (alcohol) d , which exhibits IC 50 values of 25 and 29 μM, respectively. The little or no inhibition (IC 50 > 200 μM) of LOX-3 by most other parent NSAID molecules ( a – n ), as also observed in the literature [ 17 , 18 , 19 ], supports the fact that the incorporation of the two pharmacophores in one structure leads to an improved interaction with the enzyme.…”
Section: Resultssupporting
confidence: 76%
“…The reaction was monitored for 7 min at 28 °C, recording the absorbance at 234 nm. Nordihydroguaiaretic acid (NDGA) was used as a reference [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, compounds 4 and 5 also considerably lowered lipid levels, although they presented weak or no activity in all other experiments. It could be suggested that the (methoxy)cinnamyl moiety is responsible for this effect, since it has been reported that many cinnamic acid derivatives possessed hypolipidemic activity [ 53 , 54 ]. Of course, other factors may be related to this lipid decrease in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Nordihydroguaiaretic acid was used as a reference. For the estimation of the type of inhibition, the described experiments were repeated, using sodium linoleate at a concentration (1 mM) higher than the saturating substrate concentration [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation